In vitro embryogenic callus induction of Carica pubescens Lenne and K.Koch using 2,4-D (2,4-Dichlorophenoxy Acetic Acid) and BAP (6-Benzylaminopurin) - Shinta Shinta; Eko Budi Minarno; I’anatur Rofiqoh (The East Java Biological Society, 2020)
Carica pubescens Lenne & K. Koch has benefits as a producer of medicinal compounds. Propagation of C. pubescens is important to be done through in vitro embryogenic callus culture. This research aimed to determine the effect of 2,4-D growth regulators, 2,4-D and BAP interactions on the induction of embryogenic callus C. pubescens Lenne & K. Koch. This research is experimental, using a completely randomized design (CRD) with 25 treatments and 5 replications. Embryonic callus was induced by various concentration of 2,4 D (0 mg/L, 2.5 mg/L, 5 mg/L, 7.5 mg/L, and 1 mg/L) in combination with BAP (0 mg/L, 2.5 mg/L, 5 mg/L, 7.5 mg/L, and 1 mg/L). Data were analyzed using two-way ANOVA, followed by the Duncan Multiple Range Test (DMRT) (p>0.05). The result showed that the addition of 2,4 D and BAP as a growth regulator gave an effect on embryonic callus. Concentration of 7.5 mg/L 2,4 D and 0.5 mg/L BAP in callus 19 days after planting showed the most effective interaction of both inductors. The combination produced callus fresh weight at 1.09 g and 99% in percentage of explant callus area. Morphological and anatomical observations showed the characteristic of embryogenic callus as indicated by yellowish, textured callus friable, having a large core and containing starch grains also plastids.